Autonomous safety control of flight vehicles - Yu, Xiang, 1981- (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2021)
"Aerospace vehicles are regarded as one classical type of safety-critical systems. By virtue of a safety control system, the aerospace vehicle can maintain high performance despite of component malfunctions and multiple disturbances, thereby enhancing the aircraft safety and mission success probability. This book presents a systematic methodology for improving the safety of aerospace vehicles in such aspects: the loss of control effectiveness of actuators and control surface impairments, disturbance observer-based control to against multiple disturbances, actuator faults and model uncertainties in hypersonic gliding vehicles, and faults composed by actuators faults and sensor faults. Several fundamental issues related to safety are explicitly analyzed according to aerospace engineering system characteristics. Focusing on the safety issues, the safety control design problems of aircraft are studied and elaborated in detail by using systematic design methods. The research results illustrate the superiority of the presented safety control approaches. The expected reader group for this book is undergraduate and graduate students but also industry practitioners and researchers"--
1. The Development of Safety Control Systems 2. Hybrid Fault-Tolerant Control System Design against Actuator Failures 3. Safety Control System Design against Control Surface Impairments 4. Multiple Observers based Anti-Disturbance Control for aQuadrotor UAV 5. Safety Control System Design of HGV based on Adaptive TSMC 6. Safety Control System Design of HGV based on Fixed-Time Observer 7. Fault Accommodation with Consideration of Control Authority and Gyro Availability
OCLC-licensed vendor bibliographic record.
Keywords: Airplanes -- Automatic control -- Safety measures; Flight control; TECHNOLOGY / General; TECHNOLOGY / Engineering / General; TECHNOLOGY / Engineering / Mechanical